The wages of whiteness : race and the making of the American working class - Roediger, David R. (Verso, 2007)
This is the new, fully updated edition of this now-classic study of working-class racism. Combining classical Marxism, psychoanalysis and the new labor history pioneered by E. P. Thompson and Herbert Gutman, David Roediger's widely acclaimed book provides an original study of the formative years of working-class racism in the United States. This, he argues, cannot be explained simply with reference to economic advantage; rather, white working-class racism is underpinned by a complex series of psychological and ideological mechanisms that reinforce racial stereotypes, and thus help to forge the identities of white workers in opposition to blacks. In a lengthy new introduction, Roediger surveys recent scholarship on whiteness, and discusses the changing face of labor in the twenty-first century.